Diagnosis and Surgical Management of Nonsyndromic Nine Supernumerary Teeth and Leong’s Tubercle - Christiane V. Cruz; Andrea L. Soares; David N. Braga; Marcelo C. Costa (Case Reports in Dentistry)
Nonsyndromic multiple supernumerary teeth (ST) and Leong’s tubercle are a condition with a very low prevalence and a multidisciplinary approach is required to restore function and aesthetics. So, this case report aimed at presenting a rare case of nonsyndromic nine supernumerary teeth and Leong’s tubercle in a pediatric patient, without any evident familial history, showing its diagnosis and surgical management.